(untitled) (Global Journal of Science Frontier Research, 2012)
Synthesis and antimicrobial activity of some new heterocycles such as pyrimidines, 1,2,4-triazoles, 1,2,4-triazines, 1,3-thiazoles and related compounds (2-26) bearing 1,2,4-triazine moiety have been prepared from the reaction of the 3-amino-5,6-diphenyl-1,2,4-triazine (1) with different organic reagents under different reaction conditions. Structures of the new synthesized compounds were confirmed by elemental analyses and spectral data. Some of the synthesized products were tested and evaluated as antimicrobial agents.